The human functioning revolution: implications for health systems and sciences - Bickenbach, Jerome; Rubinelli, Sara; Baffone, Cristiana; Stucki, Gerold (Frontiers in Science, 2023)
The World Health Organization (WHO) concept of human functioning represents a new way of thinking about health that has wide-ranging consequences. This article explicates this paradigm shift, illustrates its potential impact, and argues that societies can profit by implementing functioning as the third indicator of health, complementing morbidity and mortality. Human functioning integrates biological health (the bodily functions and structures that constitute a person’s intrinsic health capacity) and lived health (a person’s actual performance of activities in interaction with their environment). It is key to valuing health both in relation to individual well-being and societal welfare—operationalizing the United Nations Sustainable Development Goal (SDG) 3 principle that health is a public good. Implementing functioning as defined and conceptualized in the International Classification of Functioning, Disability and Health (ICF) could profoundly benefit practices, research, education, and policy across health systems and health strategies and help integrate health and social systems. It also offers a foundation for reconceptualizing multidisciplinary health sciences and for augmenting epidemiology with information derived from peoples’ lived experiences of health. A new interdisciplinary science field—human functioning sciences—itself holds the promise to integrate research inputs and methods from diverse biomedical and social disciplines to provide a more comprehensive understanding of human health. To realize these opportunities, we must address formidable methodological, implementation, and communication challenges throughout health systems and broader society. This endeavor is vital to orientate health systems toward what matters most to people about health, to unlock the societal economic investment in health that is essential for individual and population-level well-being, and to drive progress toward achieving the SDGs.